(untitled) (Eurasian Journal of Ecology, 2021)
The article is devoted to the description of a new representative of the family Undorosauridae, found on the territory of the West Kazakhstan region. A new genus of ichthyosaurs of the family Undorosauridae has been identified. The main diagnostic features of this family are incomplete medial fusion of the sciatic and pubic bones, as well as a peculiar structure of the skull (large nasal opening, oval eye socket, wide occipital part and the structure of the occipital part. In this work, we applied the generally accepted paleontological methods of field and laboratory research: standard procedure for working with paleontological material to extract the studied samples from the host rock; morphological and morphometric analysis of fossils in species diagnostics. The similarity in the structure of the skull, postcranial skeleton, belts, limbs allows us to attribute the described ichthyosaur skeleton to the family Undorosauridae. Geological age: late Jurassic, Middle Volga tier, Zaraiskites Zarajskensis zone. Key words: family Undorosauridae, mesozoic, middle Volga tier, Western Kazakhstan.